If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(s+3)=21
We simplify the equation to the form, which is simple to understand
2(s+3)=21
Reorder the terms in parentheses
+(+2s+6)=21
Remove unnecessary parentheses
+2s+6=+21
We move all terms containing s to the left and all other terms to the right.
+2s=+21-6
We simplify left and right side of the equation.
+2s=+15
We divide both sides of the equation by 2 to get s.
s=7.5
| 5p^2-36p=32 | | (x+4)(6x^3+10x^2-9x+3)= | | 10x+17=3x | | -0.333333333333333x=-0.333333333333333x-0.5 | | 11.74=-log(x) | | 4x-8-2x+3=-10x+7+12x+5 | | 42s+s=8322 | | 4(4x-9)+9x= | | 9x+6(80)=7x+560 | | 6y=-2x | | 8x+9=9x+7 | | 6+3x+4x^2+2x^3=0 | | (6-8i)(6+8i)= | | 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 | | 4(3x-9)-5=4(x-5)+27 | | 4y^3+27y^2+27=0 | | 27y^2+27=0 | | 3-4*6+3= | | 4(3x-8)-5=4(x-5)+15 | | (11x+26)-3= | | Y^6+9y^4-4y^3+27y^2+27=0 | | -7(2c+5)=(c-6) | | 8y-9=12y+15 | | 5x-(2x+4)=14 | | x^2-5x-2.25=0 | | Y=(3x+8)(x-9) | | 6+(3x-4)-(7x+11)= | | 8(7x-6)=27 | | x+20=5x+8 |